Low social control and physiological deregulation—the stress–disequilibrium theory, towards a new demand–control model - Karasek, Robert (SJWEH Supplements, 2008)
' ' OBJECTIVES ': 'The paper presents a new stress physiological theory to describe how low social control can contribute to the development of chronic disease through the deregulation of physiological systems. ' ' METHODS ': 'Two presumptions and four operating principles are used to derive very generalized forms of hypotheses about disease (and some hypotheses about growth) with respect to the demand–control model. They are based on a new three-part stress model (controller-system-environment) that represents a nested pair of system–environment relations in a systems dynamics formulation, with control limitations based on the Second Law of Thermodynamics, and mechanisms related to an equilibrium of flows of energy and order. The resulting “associationist” demand–control model outlines the processes by which organisms can either devolve into lower levels of complexity equivalent to chronic disease (job strain) or organize themselves into higher levels of complexity (active work). ' ' RESULTS ': 'An explanation is provided for how failures of high-level control capacity could be sufficient to explain the development of chronic disease. A new theory of the development of high-level internal control capacity in complex organisms is presented. An “association-of–parts” theoretical format is claimed to be an acceptable alternative to materialistic explanations for both health and growth. ' ' CONCLUSIONS ': 'The requirements of explaining new effects of complex work and social structures confirm the need to revise the demand–control model into a more general form.
Keywords: chronic disease; complexity theory; control; decision latitude; demand; demand–control model; disease; disequilibrium; low social control; physiological deregulation; second law of thermodynamics; social control; stress; stress–disequilibrium theory; systems theory; thermodynamics